The synthesis of extracellular vesicles by the protistan parasite Blastocystis - Leonardi, Steven Santino; Koh, Eileen Yiling; Deng, Lei; Huang, Chenyuan; Tong, Lingjun; Wang, Jiong-Wei; Tan, Kevin Shyong-Wei (Frontiers in Cellular and Infection Microbiology, 2022)
Blastocystis is a genus of single-celled protist belonging to the stramenopile group. Prior studies have shown that isolates of Blastocystis subtype 7 (ST7) induced higher levels of intestinal epithelial cell damage and gut microbiota dysbiosis in comparison to other subtypes in in vivo and in vitro settings. Prior research has shown a link between gut dysbiosis and exposure to extracellular vesicles (EVs) produced by pathogenic microorganisms. This study demonstrates a protocol for the isolation of EVs from Blastocystis ST7 via ultracentrifugation. Nanoparticle tracking analysis and transmission electron microscopy were used to assess EV size and morphology. The protein content of isolated EVs was assessed by mass spectrophotometry and the presence of EV markers were evaluated by Western blotting. Finally, the EVs were cocultured with prominent human gut microbiome species to observe their effect on prokaryote growth. Our data shows that Blastocystis ST7 secretes EVs that are similar in morphology to previously characterized EVs from other organisms and that these EVs contain a limited yet unique protein cargo with functions in host-parasite intercellular communication and cell viability. This cargo may be involved in mediating the effects of Blastocystis on its surrounding environment.